The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fncel.2020.00068
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Deaths and Potential Crosstalk With Blood–Brain Barrier Dysfunction After Hemorrhagic Stroke

Abstract: Hemorrhagic stroke is a life-threatening neurological disease characterized by high mortality and morbidity. Various pathophysiological responses are initiated after blood enters the interstitial space of the brain, compressing the brain tissue and thus causing cell death. Recently, three new programmed cell deaths (PCDs), necroptosis, pyroptosis, and ferroptosis, were also found to be important contributors in the pathophysiology of hemorrhagic stroke. Additionally, blood-brain barrier (BBB) dysfunction plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 165 publications
2
59
0
Order By: Relevance
“…Previous studies have shown that inflammation precipitated by neuroglia and infiltrating leukocytes is a significant mechanism that participates in ICH-induced brain injury. Inflammation contributes to the breakdown of the blood-brain barrier (BBB), which in turn exacerbates the inflammation by allowing the infiltration of immunocytes ( 3 5 ). Besides, blood components, such as red blood cells (RBCs), leukocytes, and plasma proteins enter the brain immediately following the hemorrhage and these infiltrations may also play a role in the progress of the disease ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that inflammation precipitated by neuroglia and infiltrating leukocytes is a significant mechanism that participates in ICH-induced brain injury. Inflammation contributes to the breakdown of the blood-brain barrier (BBB), which in turn exacerbates the inflammation by allowing the infiltration of immunocytes ( 3 5 ). Besides, blood components, such as red blood cells (RBCs), leukocytes, and plasma proteins enter the brain immediately following the hemorrhage and these infiltrations may also play a role in the progress of the disease ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, impaired mitochondrial function generates the production of superoxide radicals, reducing antioxidant activity and causing oxidative stress, which in turn results in the oxidation of proteins and lipids in the cell membrane and DNA fragmentation, ultimately leading to cell necrosis [30]. On the other hand, the events that lead to cell death in the penumbra area are more complex and can extend for weeks after ischemia [30][31][32].…”
Section: Stroke Pathophysiology 21 Overviewmentioning
confidence: 99%
“…Necroptosis and pyroptosis are two additional and important forms of programmed cell death after ischemia or hemorrhage in the brain. Both necroptosis and pyroptosis could be a result of inflammatory factors or DAMPs [4]. Recently, a paper revealed that PACAP is involved in the inhibition of necroptosis in atherosclerosis, and functions by mediating receptor interacting protein 3 (RIP3) expression, a key protein of necroptosis [159].…”
Section: Pacap and Cell Deathmentioning
confidence: 99%
“…The function and structure of BBB would be damaged after stroke, further aggravating the pathological changes. The BBB consists of the neurovascular unit, including endothelial cells, astrocytes, pericytes, neurons, and microglia [4,165]. Among them, endothelial cells and astrocytes function as the most important components of the BBB.…”
Section: Pacap and Bbb Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation